Emocje w autobiografii Władka. Metoda autobiograficzna Thomasa i Znanieckiego na tle przykładu współczesnej analizy Fritza Schützego - Nowak, Marek; Luczys, Piotr (Człowiek i Społeczeństwo, 2019)
The proposed study is an attempt to address the issue of emotions in the context of the biographical analysis proposed by W.I. Thomas and F. Znaniecki. Due to the canonical character of the work and its theoretical significance, a comparative analysis with the example of Fritz Schütze’s biographical analysis was applied, recognizing that only against the background of the contemporary research approach will the value of Thomas and Znaniecki’s work be discernible. The research idea of the authors of the article was therefore, in a way, exploratory. The conclusions of the analysis allow us to describe the status of emotions in classical and contemporary analysis; on the other hand, to critically interpret the autobiographical text of Władek (Volume III of the Book), together with the analytical work carried out on this text by both authors. The text of the article refers to excerpts from works on emotions, but also reviews the literature on the subject, concerning the perception of emotions in American sociology from the turn of the 19th and 20th centuries and from the first half of the 20th century, which gives grounds for answering questions about the sources of understanding emotions in the contemporary sociological literature. Marek Nowak, Piotr Luczys, Emocje w autobiografii Władka. Metoda autobiograficzna Thomasa i Znanieckiego na tle przykładu współczesnej analizy Fritza Schützego [Emotions in Władek’s autobiography. Autobiographical method of Thomas and Znaniecki with the example of contemporary analysis by Fritz Schütze] edited by M. Nowak, „Człowiek i Społeczeństwo” vol. XLVII: „Chłop polski w Europie i Ameryce” po stu latach [Polish peasant in Europe and America after one hundred years], Poznań 2019, pp. 57–86, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271.